2009
DOI: 10.1089/met.2008.0043
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Insulin Resistance, Glucose Intolerance, and Hypertension in Pregnancy

Abstract: There is an association between insulin resistance, glucose intolerance, and essential hypertension, but the relation between insulin resistance, glucose intolerance, and hypertension diagnosed during pregnancy is not well understood. Transient hypertension of pregnancy, the new-onset nonproteinuric hypertension of late pregnancy, is associated with a high risk of later essential hypertension and glucose intolerance; thus, these conditions may have a similar pathophysiology. To assess the association between i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 41 publications
5
16
1
Order By: Relevance
“…While most studies reported significant associations between HDP and GDM or insulin resistance [16,17,51], we did not find any association between GDM and HDP. Similar results were observed in Bangladesh and in Cameroon [52,53], where there was no difference between mean SBP and DBP among women with and without gestational diabetes.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…While most studies reported significant associations between HDP and GDM or insulin resistance [16,17,51], we did not find any association between GDM and HDP. Similar results were observed in Bangladesh and in Cameroon [52,53], where there was no difference between mean SBP and DBP among women with and without gestational diabetes.…”
Section: Discussioncontrasting
confidence: 99%
“…The food groups included cereals; white roots and tubers; vitamin A-rich vegetables and tubers; dark green leafy vegetables; other vegetables; vitamin A-rich fruits; other fruits; organ meat; flesh meat; eggs; legume, nuts and seeds; fish and sea foods; milk and milk products; oil and fats; sweets; spices, condiments and beverages. DDS was divided into three categories and classified as low (0-5), medium (6-8) and high (9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between maternal MS and hyperglycemia during pregnancy was first reported by Bo et al [27] and has been recently corroborated by our research group [28, 29]. Thus, in addition to the 13–15 % rates of pregestational DM observed in the present study, the overweight and obese groups were expected to show elevated rates of MGH or GDM, and a high proportion of HbA1c ≥ 6.5 %.…”
Section: Discussionsupporting
confidence: 89%
“…33,34 Finding of our study i.e. high blood pressure (>140/90 mmHg), high fasting blood sugar level (>110 mg %), high serum triglycerides (>150 mg %), low HDL-C (< 39mg%) satisfied all three criteria i.e.…”
Section: Discussionmentioning
confidence: 64%